Clinicopathological Profile and Malignant Transformation in Oral Lichen Planus: A Retrospective Study - Bandyopadhyay, Alokenath (J Int Soc Prev Community Dent, 2017)
OBJECTIVES: The aim of this study was to analyze the histopathologically diagnosed cases of oral lichen planus (OLP) in terms of age, gender, clinical variant, site, hyperpigmentation, systemic illness, grade of dysplasia, and associated malignant transformation. This study also intended to do a review of reported cases of OLP with malignant transformation. MATERIALS AND METHODS: One hundred and forty-three cases of histopathologically diagnosed OLP between 2010 and 2016 were retrospectively reviewed. Demographic and clinicopathological data including malignant transformation were obtained. The data obtained were analyzed using the Statistical Package for the Social Sciences (SPSS) software for Windows version 20.0 (IBM SPSS, SPSS Inc., Chicago, IL, USA). A review of published literature on OLP with malignant transformation was also done from 1988 to 2017 and tabulated. RESULTS: OLP in this study showed a male predilection with most of the patients in the third decade. The buccal mucosa (bilateral presentation) was the most common site (79.72%), and reticular type was the most common clinical type (79.02%) followed by erosive type (20.98%). The majority (92.31%) of cases were diagnosed with OLP without dysplasia. The rest (7.69%) of dysplastic cases were predominantly seen in the buccal mucosa of 58 years and above, female patients manifesting mainly as erosive type. Two patients (1.4%) previously diagnosed clinically and histopathologically as OLP developed oral squamous cell carcinoma. CONCLUSION: The present investigation revealed the predominance of OLP among middle-aged male population and the prevalence of bilateral involvement of buccal mucosa. Two of our cases showed malignant transformation over an average period of 3.5 years. The outcome of this study emphasizes the role of clinical follow-up of patients with OLP.